Speak well - O'Brien, Liz
Liz O'Brien teaches students that to speak well is to speak responsibly, confidently, and authentically--to create well-researched and constructed speeches, and to converse, and connect with their audience. Through Speak Well's listener-centered approach to public speaking, one in which the speaker engages in a vibrant conversation with listeners rather than giving a static performance, students learn that their primary purpose as speakers is to communicate ideas. The result is reduced student anxiety about speech delivery, increased self-assurance, and more authentic, successful speeches